2019
DOI: 10.1002/jbmr.3667
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Myosin X Enhances Osteoclastogenesis and Increases Cell Surface Unc5b in Osteoclast-Lineage Cells

Abstract: Normal bone mass is maintained by balanced bone formation and resorption. Myosin X (Myo10), an unconventional “myosin tail homology 4‐band 4.1, ezrin, radixin, moesin” (MyTH4‐FERM) domain containing myosin, is implicated in regulating osteoclast (OC) adhesion, podosome positioning, and differentiation in vitro. However, evidence is lacking for Myo10 in vivo function. Here we show that mice with Myo10 loss of function, Myo10m/m, exhibit osteoporotic deficits, which are likely due to the increased OC genesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…These results were confirmed by shRNAs-mediated Myo10 silencing in primary mouse osteoclasts (Box 3), which also showed that osteoclast differentiation was affected (Tasca et al, 2017). In contrast to these reports, a recent study found that Myo10 KO osteoclasts differentiated more efficiently (Wang et al, 2019). The actual bone resorption activity of was not assessed, but the serum of the mice contained high levels of bone resorption marker deoxypyridinoline, suggesting Myo10 KO osteoclasts were active in vivo (Wang et al, 2019).…”
Section: Actin and Microtubule Crosstalk At The Podosome Beltmentioning
confidence: 72%
See 1 more Smart Citation
“…These results were confirmed by shRNAs-mediated Myo10 silencing in primary mouse osteoclasts (Box 3), which also showed that osteoclast differentiation was affected (Tasca et al, 2017). In contrast to these reports, a recent study found that Myo10 KO osteoclasts differentiated more efficiently (Wang et al, 2019). The actual bone resorption activity of was not assessed, but the serum of the mice contained high levels of bone resorption marker deoxypyridinoline, suggesting Myo10 KO osteoclasts were active in vivo (Wang et al, 2019).…”
Section: Actin and Microtubule Crosstalk At The Podosome Beltmentioning
confidence: 72%
“…In contrast to these reports, a recent study found that Myo10 KO osteoclasts differentiated more efficiently (Wang et al, 2019). The actual bone resorption activity of was not assessed, but the serum of the mice contained high levels of bone resorption marker deoxypyridinoline, suggesting Myo10 KO osteoclasts were active in vivo (Wang et al, 2019). Of note, Myo10 KO osteoclasts derived from The function of kinesins, microtubule-associated motors, is mostly unstudied in osteoclasts thus far.…”
Section: Actin and Microtubule Crosstalk At The Podosome Beltmentioning
confidence: 89%
“…We then evaluated axonal growth and midline crossing in control and MyoX-KO cortical neurons. MyoX-KO cortical neurons were achieved by IUE of Cre-GFP or GFP (as a control) into the neocortex of Myo X f/f embryos (at E15.5; Wang et al, 2019 ); and the electroporated brain samples were examined at P7, a critical time window for cortical neuronal axon growth and midline crossing ( Tagawa and Hirano, 2012 ; Fenlon and Richards, 2015 ). To our surprise, axons of Myo X-KO (Cre-GFP + ) neurons crossed the midline, and their lengths were comparable to those of control axons ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Myo X f/f mice were generated as previously described ( Wang et al, 2019 ), and Netrin-1 floxed (NTN1 f/f ) mice were kindly provided by Yu-Qiang Ding (Fudan University, Shanghai, China). All the mouse lines indicated above were maintained on a C57BL/6 background for more than six generations.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10] With further studies, researchers have developed an oligopeptide that can significantly reduce and inhibit the osteoclastic ability of bone marrowderived macrophages (BMMs), and achieve reduce excessive bone absorption. 11,12 In this study, we designed a drug delivery system that can fully and effectively deliver these molecules to BMMs. This will improve the precision and potency of the treatment.…”
Section: Introductionmentioning
confidence: 99%